Stå på tomma torg: Hinder för tillhörighet i bosnisk migrationslitteratur - Borcak, Fedja Wierød (K&K - Kultur og Klasse, 2018)
The immigration of Bosnians to the Scandinavian countries in connection to the war in the 1990s is largely seen as a success. Aspects such as high employment and education levels has been foregrounded as indicating integration and personal accomplishment, especially among the younger population. However, the literature produced by Bosnian immigrant authors tells a different story, which focuses rather on personal hardships and obstacles in the affective and social “positionality” of the immigrant in the Scandinavian topography. Regarding texts by authors such as Alen Mešković, Bekim Sejranović, and Adnan Mahmutović, the article surveys recurrent themes associated with the immigrant’s inability to create belonging in the host country, such as the encounter with immigrant authorities or the continuous non-contact with Scandinavians. While the texts are not typical examples of literary “welfare criticism”, the article tries to suggest some ways in which these texts produce critique of mechanisms in the Scandinavian welfare state model.